Desenvolvimento de aplicativo móvel de carteirinha digital de vacinação - Owada, Fernanda Hideko do Nascimento (Brasil, 2022)
The vaccination is one of most effective public health interventions in the world, and during the pandemic time, the use of digital technologies revolutionized the dose registration system in Brazil, which can be accessed digitally. Although, this resource doesn’t apply to the other vaccines, therefore, brazilians doesn't have a record of the previous vaccination that is trustable and with an easy access, having in mind that the current one is made on paper, opening possibilities to be easily damaged and to get lost, resulting in the total loss of information. Therefore, this project has the objective of making use of the digital design, user experience and information design for a digital vaccination card app development, providing an efficient dose record, and a bigger personal data monitoring, access of quality information, encouraging people to vaccinate and give the right of health and to life. The project execution used the Double Diamond of the Design Thinking methodology, which was divided in 4 steps: Discover, Define, Develop and Deliver. During the development were made similar analysis, personas definitions, and empathy map, CSD matrix, briefing, requirements and parameters, userflow, sitemap, questionnaire and low-fidelity, mid-fidelity and high-fidelity wireframes. Finally, was elaborated an interface prototype for the application, evidencing the most important screens flows and its functions, attached to a style guide document containing the main design guidelines.